2005
DOI: 10.1111/j.1365-2141.2005.05745.x
|View full text |Cite|
|
Sign up to set email alerts
|

Multicentre phase III trial on fludarabine, cytarabine (Ara‐C), and idarubicin versus idarubicin, Ara‐C and etoposide for induction treatment of younger, newly diagnosed acute myeloid leukaemia patients

Abstract: Summary Fludarabine plus cytarabine (Ara‐C) and idarubicin (FLAI) is an effective and well‐tolerated induction regimen for the treatment of acute myeloid leukaemia (AML). This phase III trial compared the efficacy and toxicity of FLAI versus idarubicin plus Ara‐C and etoposide (ICE) in 112 newly diagnosed AML patients <60 years. Fifty‐seven patients received FLAI, as the first induction–remission course, and 55 patients received ICE. Post‐induction treatment consisted of high‐dose Ara‐C (HDAC). After HDAC, pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 29 publications
3
43
0
1
Order By: Relevance
“…Some of these issues were prospectively evaluated by the recent randomized AML15 MRC trial in which investigators showed that FLAG-Ida achieved more CRs than daunorubicin 1 cytarabine (3 1 7) [23]. Similar conclusions, although on a smaller series of patients, had been drawn in an Italian randomized study comparing FLAG-Ida and Idarubicin, etoposide and Ara-C [36]. Furthermore, we recently retrospectively compared fludarabinecontaining and conventional induction regimens in NPM-mut AML patients and showed that FLAI-5, if compared to standard 3 1 7, resulted in significantly higher CR rates (86% vs. 69% with FLAI-5 and 3 1 7, respectively, P 0.021) and longer DFS at 24 months (P < 0.001) [37].…”
Section: Discussionmentioning
confidence: 48%
“…Some of these issues were prospectively evaluated by the recent randomized AML15 MRC trial in which investigators showed that FLAG-Ida achieved more CRs than daunorubicin 1 cytarabine (3 1 7) [23]. Similar conclusions, although on a smaller series of patients, had been drawn in an Italian randomized study comparing FLAG-Ida and Idarubicin, etoposide and Ara-C [36]. Furthermore, we recently retrospectively compared fludarabinecontaining and conventional induction regimens in NPM-mut AML patients and showed that FLAI-5, if compared to standard 3 1 7, resulted in significantly higher CR rates (86% vs. 69% with FLAI-5 and 3 1 7, respectively, P 0.021) and longer DFS at 24 months (P < 0.001) [37].…”
Section: Discussionmentioning
confidence: 48%
“…This approach may make it possible to obtain, with a single course of treatment, a rate of CR comparable with that achieved using intensified induction for all patients (Bishop et al, 1996;Russo et al, 2005) but with a reduction in the overall toxicity. There are two potential advantages (a) no intensification for patients who do not need it; (b) patients The ranges of distribution of the ratios between baseline and daily absolute blast count, converted to a logarithmic scale (Log Reduction), have minimal overlap between CR and NCR groups.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 In patients with relapsed AML, depending on cytogenetic profile, age and time of first remission, cytarabine-based salvage chemotherapy is sometimes satisfactory. 15,18,19 However, only a few randomized studies address this issue, which thus remains a gray area. 20,21 In second line setting, favorable, intermediate or high intermediate group are suitable to SWOG 9126 protocol (high dose cytarabine, daunorubicin and cyclosporine).…”
Section: Discussionmentioning
confidence: 99%